Estimating the validity of Tanaka-Johnston and Moyer's analysis of a Saudi sample - Ahmad A. Al-Fraidi; Abdulsamad Talaat Habeeb; Sarah Awadh Alserhani; Raood Talal Al-Kaki; Saleh Saeed Alkhathami; Hadeel Ahmed Bafaqeeh (Wolters Kluwer Medknow Publications, 2024)
OBJECTIVES: Accurate estimation of unerupted permanent canines and premolars is a crucial step for effective orthodontic treatment planning during mixed dentition. This study aimed to evaluate the validity of Moyers' charts and the Tanaka-Johnston equation in predicting tooth sizes in a sample of the Madina population in Saudi Arabia and propose a new regression equation. METHODS: Dental casts from 219 subjects (113 males and 106 females) were analyzed. Actual mesiodistal tooth widths were measured using digital calipers with an accuracy of 0.01 mm. Moyers' and Tanaka-Johnston predictions were compared with actual measurements, and a new set of prediction equations was developed. RESULTS: Tanaka-Johnston predictions consistently overestimated the actual measurements, exhibiting a difference of 1.20 mm for maxillary canines and premolars and a difference of 1.25 mm for mandibular teeth. The Moyers chart showed gender-specific variations with males aligning with the 50th percentile and females aligning with the 65th percentile for upper arches and the 50th percentile for lower arches. Newly derived linear regression equations were established for predicting the sum of upper and lower canines and premolars for the Madina population. CONCLUSION: The study highlights limitations in the Moyers and Tanaka-Johnston methods used for the current sample as both methods overestimated tooth sizes. New regression equations were developed to offer a more accurate approach for predicting tooth sizes for the study sample.